BIOHEMIJSKI INDIKATORI INFLAMATORNOG ODGOVORA KOD PACIJENATA SA LEUKEMIJOM I FLEBITISOM POVEZANIM SA PICC-OM: PROCENA OSNOVNOG FAKTORA RASTA FIBROBLASTA U KOMBINACIJI SA TERAPIJOM SVETLOM: Light and bFGF Therapy for PICC-Related Phlebitis in Leukemia - Zhang, Shurong; Yang, Xiaotian; Zhang, Xingxia; Wan, Yan; Yu, Youhuan (Journal of Medical Biochemistry, 2025)
Background: The primary objective was to assess the effectiveness and safety of combined bFGF and light therapy for Peripherally Inserted Central Catheters (PICC) phlebitis, measuring improvements in phlebitis grading and Visual Analogue Scale (VAS) scores; evaluating inflammatory regulation through C-reactive protein (CRP), procalcitonin (PCT), erythrocyte sedimentation rate (ESR), and interleukin-6 (IL-6); and determining quality of life changes using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), to establish whether combined therapy demonstrates statistically significant advantages over standard care. Methods: This retrospective study included leukemia patients aged 18-75 years with PICC-associated phlebitis at Huai’an Second People’s Hospital between January 2019 and December 2024. Patients were divided into an intervention group (n=33) receiving combined bFGF and light therapy, and a control group (n=32) receiving standard care. Assessment metrics included phlebitis scores and VAS pain scores evaluated on days 3 and 7; inflammatory markers (CRP, PCT, ESR, IL-6) and QLQ-C30 scores assessed on day 7. Data were analyzed using SPSS 26.0, with t-tests for between-group comparisons (P<0.05 considered statistically significant). The study received ethics committee approval, and all participants provided informed consent. Results: Baseline characteristics were similar between groups. In the intervention group, phlebitis scores decreased from 2.22 (±1.08) at baseline to 0.18 (±0.46), and VAS scores from 5.4 (±2.8) to 0.55 (±1.37), significantly outperforming the control group (p<0.001). Regarding inflammatory markers, by day 7, the intervention group showed reductions in CRP to 4.32 mg/L (±4.20), PCT to 0.15 ng/ml (±0.24), ESR to 8.45 mm/h (±9.25), and IL-6 to 4.79 pg/ml (±6.37), all significantly superior to the control group (P<0.001). In QLQ-C30 scores, the intervention group demonstrated significant improvements in physical, role, cognitive, and social functioning, as well as overall health, with marked reductions in fatigue, pain, insomnia, and appetite loss (P<0.05). No adverse events were reported in the intervention group, while 18.8% of control group patients experienced complications requiring additional intervention. Conclusion: This study confirms that combined basic fibroblast growth factor and light therapy significantly improves outcomes in managing PICC-associated phlebitis in leukemia patients. This combined approach effectively relieves pain, reduces inflammatory response, and significantly enhances overall comfort and quality of life with excellent safety profiles, offering a promising new strategy for clinical management of PICC phlebitis. Larger prospective studies with longer follow-up periods are needed to further validate the long-term efficacy and optimize clinical applications of this combined treatment regimen.